Assessment of attenuation of varicella-zoster virus vaccines based on genomic comparison - Moon, Jae Yun; Seo, Jina; Lee, Jaewoo; Park, Daechan (Journal of Medical Virology, 2023)
Live attenuated varicella-zoster virus (VZV) vaccines are used to prevent chickenpox and shingles. Single nucleotide polymorphisms (SNPs) that occur during the attenuation of parental strains are critical indicators of vaccine safety. To assess the attenuation of commercial VZV vaccines, genetic variants were comprehensively examined through high-throughput sequencing of viral DNA isolated from four VZV vaccines (Barycela, VarilRix, VariVax, and SKY Varicella). Whole-genome comparison of the four vaccines with the wild-type strain (Dumas) revealed that the sequences are highly conserved on a genome-wide scale. Among the 196 common variants across the four vaccines, 195 were already present in the genome of the parental strain (pOka), indicating that the variants occurred during the generation of the parental strain from the Dumas strain. Compared to the pOka genome, the vaccines exhibited distinct variant frequencies on a genome-wide and within an attenuation-related open reading frame. In particular, attenuation-associated 42 SNPs showed that Barycela, VarilRix, VariVax, and SKY Varicella are in ascending order regarding similarity with pOka-like genotypes, which in turn, might provide genomic evidence for the levels of attenuation. Finally, the phylogenetic network analysis demonstrated that genetic distances from the parental strain correlated with the attenuation levels of the vaccines.
Keywords: Chickenpox; Chickenpox Vaccine; Genomics; Herpes Zoster; Herpes Zoster Vaccine; Herpesvirus 3, Human; Humans; Phylogeny; Vaccines, Attenuated; attenuation; genomic comparison; single-nucleotide polymorphism; varicella-zoster virus; whole-genome sequencing